2017
DOI: 10.1111/1744-7917.12445
|View full text |Cite
|
Sign up to set email alerts
|

Potato aphid Macrosiphum euphorbiae performance is determined by aphid genotype and not mycorrhizal fungi or water availability

Abstract: Intra-and interspecific variation in plant and insect traits can alter the strength and direction of insect-plant interactions, with outcomes modified by soil biotic and abiotic conditions. We used the potato aphid (Macrosiphum euphorbiae Thomas) feeding on cultivated Solanum tuberosum and wild Solanum berthaulti to study the impact of water availability and plant mutualistic arbuscular mycorrhizal (AM) fungi on aphid performance and susceptibility to a parasitoid wasp (Aphidius ervi Haliday). Plants were grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…Intraspecific variation in R. padi mass gain in the present study was attributed mainly to aphid genotype and not to H. defensa infection (Fig. B), with individuals belonging to genotype E generally performing poorly compared with genotypes A and B. Aphid genotype is often identified as a key determinant of aphid performance, for example in S. avenae (Figueroa et al ., ) and M. euphorbiae (Karley et al ., ). A recent study reported that M. euphorbiae genotypes capable of forming endosymbiotic associations with H. defensa had higher fitness than those genotypes which did not support H. defensa infection, at least when feeding on a susceptible host plant species (Clarke et al ., ), which contrasts with the findings for R. padi lines assessed in the current study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Intraspecific variation in R. padi mass gain in the present study was attributed mainly to aphid genotype and not to H. defensa infection (Fig. B), with individuals belonging to genotype E generally performing poorly compared with genotypes A and B. Aphid genotype is often identified as a key determinant of aphid performance, for example in S. avenae (Figueroa et al ., ) and M. euphorbiae (Karley et al ., ). A recent study reported that M. euphorbiae genotypes capable of forming endosymbiotic associations with H. defensa had higher fitness than those genotypes which did not support H. defensa infection, at least when feeding on a susceptible host plant species (Clarke et al ., ), which contrasts with the findings for R. padi lines assessed in the current study.…”
Section: Discussionmentioning
confidence: 97%
“…A recent study reported that M. euphorbiae genotypes capable of forming endosymbiotic associations with H. defensa had higher fitness than those genotypes which did not support H. defensa infection, at least when feeding on a susceptible host plant species (Clarke et al ., ), which contrasts with the findings for R. padi lines assessed in the current study. Differential effects of aphid genotype on fitness might also depend, however, on plant suitability for aphids (Karley et al ., ). In general, all R. padi genotypes examined in the present study performed poorly on the wild species HsP5 compared with the commercial barley cultivar Concerto, indicating that HsP5 is partially resistant to aphids irrespective of aphid genetic variation.…”
Section: Discussionmentioning
confidence: 97%
“…This method has been used extensively and consistently results in mycorrhizal colonisation of plant roots (e.g. Bennett et al, 2016;Karley et al, 2017). Notably, soil sterilisation removes most soil organisms, and the addition of AM fungal inocula adds both AM fungi and microbes associated with or co-extracted with the AM fungi.…”
Section: Study Site and Field Samplingmentioning
confidence: 99%
“…Insecticide‐resistant M. persicae clones are thought to survive poorly at low temperatures (Foster et al, ), and perform less well than susceptible M. persicae clones on favourable host plant species (Silva et al, ). A recent study suggested that a parasitism‐resistant line of M. euphorbiae performed less well than susceptible lines on unfavourable Solanum hosts (Karley et al, ), which might cause poor persistence of the resistant genotype in diverse vegetation. This study highlights the importance of understanding the different selection pressures imposed by aphid parasitoids and insecticides, and the effects on aphid behaviour, performance and genotype persistence, which could alter the efficacy of biological and chemical controls in agroecosystems.…”
Section: Resultsmentioning
confidence: 99%